Analisis Kualitas Pelayanan di Restoran Saung Mirah, Bogor - Subakti, Agung Gita (Bina Nusantara University, 2014)
A restaurant is one of the facilities to carry out Food Service Industry or as a part tourismÂ accommodation that plays a role in fulfilling the needs of tourists or customer. In this case, good service quality will determine the progress of a restaurant beside food and beverage as the offered products. Saung Mirah Restaurant Bogor is a restaurant that has a quality of service that is not as expected, thus causing a lot of complaints from guests. The purpose of this study is to look at the implementation of quality of service performed and what improvements could be given to the management of Saung Mirah Restaurant Bogor, so the quality of the restaurant service can be increased and complaints from customers can be decreased.